Navigating the court: A comparison of distance demands between sexes in grand slam tennis - Armstrong, C.; Peeling, P.; Murphy, A.; Reid, M. (Journal of Sports Science & Medicine, 2023)
This study analysed critical movement demands of tennis match-play to better inform contemporary approaches to athlete preparation and training. HawkEye data from matches during the 2021 and 2022 Australian Open were utilised. Distance was aggregated for movement cycles, points, games, sets, and matches, alongside total shots played. Data was collated for males (best-of-five sets) and females (best-of-three sets) allowing comparisons both within and between sexes. Overall, no differences within sexes were evident for total distance, however males traversed further per match than females (MDE = 809 ± 139m, ES = 0.86). Female players travelled further in their deciding (third) sets compared to set 1 (ES = 0.28) and while this effect wasn`t as discernible for males, the deciding (fifth) set showed some evidence of elevated distance requirements and variability. Between sexes, only female set 3 was different to male set 3 (ES = 0.29). Female and male tiebreak games (i.e. game 13) required players travel further distance compared to other games (ES = ~1.45). Between sex differences were observed for tiebreak games compared to games 1 to 12 (female ES = 1.36 and male ES = 1.53). Players from both sexes generally covered similar distances during points and movement cycles, with between-shot distances of 4.2m-4.5m, notably longer than previous reports. Further, total shots and total match distance (r > 0.97; p < 0.01) shared similar linear relationships. These results highlight that the between shot or movement cycle demands of professional hard court tennis are substantially higher than described in the literature (Roetert et al., 2003). The findings also reveal competitiveness as a key influence on set level distance demands during professional tennis match-play, a consideration in player preparation programs.